Economic evaluation of the Sin Tax Reform Act for alcohol and smoking in the Philippines - Seah, Bryan Kai Wen (Nanyang Technological University, 2022)
In the Philippines, a consistently high prevalence of smoking and alcohol has resulted in a multitude of adverse health consequences for many Filipinos. In response to the rising public health burden, policymakers have been prompted to implement taxation policies to reduce the prevalence of smoking and alcohol. The Sin Tax Reform Act (STL) was thus introduced in 2012 with the primary aim to improve public health. The purpose of this study is thus to evaluate whether the STL has been effective in reducing tobacco and alcohol consumption. With the datasets provided from Republic of Philippines Department of Science and Technology – Food and Nutrition Research Institute (DOST-FNRI), we use Ordinary Least Squares (OLS), Logistic and Tobit regressions to analyse the relationship between the increase in taxes and consumption level of tobacco and alcohol products. To address the missing data issue for smoking variable, a categorical variable was transformed into a dichotomous variable to produce a dependent variable suitable for logit regression. We find that taxes on tobacco reduced prevalence of smoking by 15.4% from 2008 to 2018, whereas drinking prevalence had increased significantly. With respect to drinking intensity however, a reduction by 0.246 units was found. We also found a significant reduction in smoking prevalence across all demographic groups such as gender, education, wealth, urbanity, age, and occupation status. Despite the taxes on alcohol products, we observe a significant increase in drinking prevalence across the demographic groups. Drinking intensity has seen a significant decline for both gender and those aged 20 to 29 years old. In conclusion, our study revealed that STL had been successful in reducing the consumption of tobacco. Whereas for alcohol, our results showed that taxes on alcohol products have not been as effective in reducing consumption in the Philippines over the years since the implementation of the STL. The upwards trend for alcohol consumption over the years thus suggests a need for policymakers to consider further increases in taxations on alcohol product in order to improve the pass-through rate.